2021
DOI: 10.1103/physrevmaterials.5.023604
|View full text |Cite
|
Sign up to set email alerts
|

Structural twinning-induced insulating phase in CrN (111) films

Abstract: Electronic states of a correlated material can be effectively modified by structural variations delivered from a single-crystal substrate. In this letter, we show that the CrN films grown on MgO (001) substrates have a (001) orientation, whereas the CrN films on α-Al2O3 (0001) substrates are oriented along (111) direction parallel to the surface normal. Transport properties of CrN films are remarkably different depending on crystallographic orientations. The critical thickness for the metal-insulator transitio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…We found that H EB reduced with increasing temperature and reached zero value at the blocking temperature (T B ) ≈150 K (Figure S9, Supporting Information), consistent with the T N of antiferromagnetic CrN layers. [32][33][34][35] The transition temperature of H EB shifted to a high temperature as R increases. This strategy provides a convenient and continuous way to tune the magnetic properties of freestanding membranes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that H EB reduced with increasing temperature and reached zero value at the blocking temperature (T B ) ≈150 K (Figure S9, Supporting Information), consistent with the T N of antiferromagnetic CrN layers. [32][33][34][35] The transition temperature of H EB shifted to a high temperature as R increases. This strategy provides a convenient and continuous way to tune the magnetic properties of freestanding membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group reported the fabrication of high-crystalline stoichiometric CrN ultrathin films using the pulsed laser deposition (PLD) technique. [32][33][34][35] The specimens were prepared by laser ablating from a high-pressure synthesized stoichiometric target and compensating the NVs using an in situ atomic nitrogen plasma source. The CrN thin films fabricated in this manner exhibited a paramagnetic-to-antiferromagnetic transition at a temperature close to its bulk value ≈283 K, [36,37] indicating the correct stoichiometry of high-quality CrN films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows a first-order magnetostructural transition from a high-temperature paramagnetic cubic (Fm-3m) to a low-temperature antiferromagnetic (AFM) orthorhombic (Pnma) phase. In the literature, the transition temperature (T N ) of CrN varies from nearly room temperature to 100 K or even gets completely suppressed depending on the Cr/N ratio [18], polycrystalline/epitaxial nature, compressive/tensile strain [19,20], thickness [19,21], choice of substrates as well as substrate orientations [20,22]. Given the fundamental [2,23,24] and technological interest [25], some experimental and theoretical works have already been done on CrN and the structural and magnetic properties of CrN are well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fundamental [2,23,24] and technological interest [25], some experimental and theoretical works have already been done on CrN and the structural and magnetic properties of CrN are well understood. However, the optical and electrical properties of CrN have been rather controversial and the underlying electronic structure of CrN received significant attention [19,20,22,23,[26][27][28][29][30]. Quintela et al [29] found semiconducting behavior in the paramagnetic phase with an activation energy of 75 meV but concluded that in the AFM phase the electrical resistivity behavior was neither conventional semiconducting nor fully itinerant.…”
Section: Introductionmentioning
confidence: 99%